Developing the digital economy in ASEAN - Chen, Lurong; Kimura, Fukunari (Routledge, 2019)
This book advances the international debate on the development of e-commerce with focus on emerging ASEAN economies. It provides readers insights on Asia's needs and efforts to improve the regional legal and economic conditions to support e-commerce. This book looks atthe rules and regulations on e-commerce, and e-commerce for inclusiveness growth. It provides insights from several ASEAN member states and discovers the requirements for Asian countries to better grasp the new juncture of growth associated with economic digitalization, which also have deep implications on continuous regional integration and community-building
Keywords: Electronic commerce / Southeast Asia; Information technology / Economic aspects / Southeast Asia; Economic development / Southeast Asia